Effect of mutual coupling and antenna correlation on MIMO system in three-dimensional spatial channel models - Jie ZHOU; Jing-feng CHEN; Lin QIU; Kikuchi HISAKAZU (Tongxin xuebao)
A channel model for frequency nonselective Rayleigh fading MIMO channel was set up and the channel model setting was extended to three-dimensional space.The mutual coupling between antenna elements was analyzed based on the equivalent network model of the multiple-antenna.The general spatial correlation expressions of channel model with the impact of mutual coupling were derived in the three-dimensional spatial channels.When the receivers were different antenna arrays,the effect of the angular parameters associated with the mean azimuth of arrival(MAOA),azimuth spread(AS),meant elevation of arrival(MEOA)and elevation spread(ES)on the MIMO system capacity was investigated.Numerical results verifiy the impact of different angle spread on spatial correlation with the mutual coupling and indicate that the system capacity is more dependent on the MAOA and MEOA than the AS and ES.